Results of a national mass media campaign in India to warn against the dangers of smokeless tobacco consumption. Issue 1 (20th April 2011) - Murukutla, Nandita; Turk, Tahir; Prasad, C V S; Saradhi, Ranjana; Kaur, Jagdish; Gupta, Shefali; Mullin, Sandra; Ram, Faujdar; Gupta, Prakash C; Wakefield, Melanie
Abstract : Objective: Smokeless tobacco consumption in India is a significant source of morbidity and mortality. In order to educate smokeless tobacco users about the health harms of smokeless tobacco and to denormalise tobacco usage and encourage quitting, a national television and radio mass media campaign targeted at smokeless tobacco users was aired for 6 weeks during November and December 2009. Methods: The campaign was evaluated with a nationally representative household survey of smokeless tobacco users (n=2898). The effect of campaign awareness was assessed with logistic regression analysis. Results: The campaign affected smokeless tobacco users as intended: 63% of smokeless-only users and 72% of dual users (ie, those who consumed both smoking and smokeless forms) recalled the campaign advertisement, primarily through television delivery. The vast majority (over 70%) of those aware of the campaign said that it made them stop and think, was relevant to their lives and provided new information. 75% of smokeless-only users and 77% of dual users said that it made them feel concerned about their habit. Campaign awareness was associated with better knowledge, more negative attitudes towards smokeless tobacco and greater cessation-oriented intentions and behaviours among smokeless tobacco users. Conclusions: Social marketing campaigns that utilise mass media are feasible and efficacious interventions for tobacco control in India. Implications for future mass media tobacco control programming in India are discussed.